Understanding access to healthcare among Indigenous peoples: A comparative analysis of biomedical and postcolonial perspectives. Issue 3 (25th March 2018) - Horrill, Tara; McMillan, Diana E; Schultz, Annette S H; Thompson, Genevieve
Abstract : As nursing professionals, we believe access to healthcare is fundamental to health and that it is a determinant of health. Therefore, evidence suggesting access to healthcare is problematic for many Indigenous peoples is concerning. While biomedical perspectives underlie our current understanding of access, considering alternate perspectives could expand our awareness of and ability to address this issue. In this paper, we critique how access to healthcare is understood through a biomedical lens, how a postcolonial theoretical lens can extend that understanding, and the subsequent implications this alternative view raises for the nursing profession. Drawing on peer‐reviewed published and gray literature concerning healthcare access and Indigenous peoples to inform this critique, we focus on the underlying theoretical lens shaping our current understanding of access. A postcolonial analysis provides a way of understanding healthcare as a social space and social relationship, presenting a unique perspective on access to healthcare. The novelty of this finding is of particular importance for the profession of nursing, as we are well situated to influence these social aspects, improving access to healthcare services broadly, and among Indigenous peoples specifically.